Audit of ultrasound guided core needle biopsies of ipsilateral axiliary lymph nodes in breast cancer - Balolebwami, David Akilimali (My University, 2021)
INTRODUCTION: The most essential prognostic factor in the management of primary breast cancer patients is the involvement of axillary lymph nodes. Ultrasound-guided core needle biopsy (US-guided CNB) of lymph nodes is a simple and minimally invasive technique used to stage the axilla. AIM: This study aims to establish the clinical usefulness and the diagnostic accuracy of US-guided CNB in targeting metastatic axillary lymph nodes. METHOD: This study is a retrospective review of US-guided CNB of ipsilateral axillary lymph nodes in breast cancer patients. Nodal ultrasound findings were considered suspicious for metastases when one of the following features was visualized: nodal enlargement (>2cm), cortical thickening (>3mm), loss of fatty hilum and non-hilar blood flow (NHBF). US-guided CNB histopathological were compared to axillary lymph node dissection (ALND) histology results for diagnostic accuracy. RESULTS: Axillary nodal metastases were found by US-guided CNB in 120/132 (90,9%) patients. Axillary lymph node dissection was performed in 63/130 (48,4%) patients, 56/63 (88,8%) and 7/63 (11,1%) of these patients had positive and negative US-guided CNB results respectively. In this study, there were no false-positive results, the false-negative result was 1/7. It was found that NHBF had a PPV of 89,8% (p=0,05), identifying a significant difference between histologically involved and non-involved nodes. Among the US-depicted abnormalities, thickening of the cortex had the highest sensitivity 91/118 (77,1%), followed by the absence of fatty hilum 84/119 (70.6%) whereas the size of the node had the highest specificity 36/37 (97,3%). CONCLUSIONS: Axillary lymph nodes in breast cancer patients can be sampled with high accuracy using the US-guided CNB technique
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Radiology Diagnostic, 2021